2012
DOI: 10.1590/s0102-695x2012005000056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of leaves of Kalanchoe pinnata and K. crenata in sun and shade conditions, as a support for their identification

Abstract: Kalanchoe pinnata (Lam.) Pers. and K. crenata (Andrews) Haw., Crassulaceae, are popularly used in the treatment of many diseases. Their biological activities, such as anti-leishmaniasis and analgesic, can be useful in phytotherapy. Both species are often misidentified as the other, because of their similar popular uses and names, and the similar external morphology of the leaves. We investigated the existence of anatomical characters that will permit correct identification of the species grown in shade and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
(26 reference statements)
3
24
0
2
Order By: Relevance
“…Some recent studies have shown that its phenolic composition can vary according to light conditions. This aspect has been observed in in vitro cultivation under blue light [24], under natural conditions in different collecting seasons [25], under light and shade [26] and in a greenhouse under UV-A and blue light [27]. In this last study, we found that supplemental blue light increased the antioxidant activity of plant extracts and caused changes in the phenolic profile of these extracts [27].…”
Section: Introductionsupporting
confidence: 64%
“…Some recent studies have shown that its phenolic composition can vary according to light conditions. This aspect has been observed in in vitro cultivation under blue light [24], under natural conditions in different collecting seasons [25], under light and shade [26] and in a greenhouse under UV-A and blue light [27]. In this last study, we found that supplemental blue light increased the antioxidant activity of plant extracts and caused changes in the phenolic profile of these extracts [27].…”
Section: Introductionsupporting
confidence: 64%
“…Phenolic idioblasts were detected earlier in the epidermis of Kalanchoë crenata (Andrews) Haw. (Moreira et al 2012) and Kalanchoë daigremontiana Raym.-Hamet and H. Perrier leaves (Chernetskyy et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the presence of phenolic-producing cells located in the mesophyll of Inula viscosa (L.) Aiton leaves (Nikolakaki and Christodoulakis 2004) as well as Crassula multicava Lem. (Castro and Demarco 2008) and several Kalanchoë species (Leal-Costa et al 2010;Moreira et al 2012;Chernetskyy et al 2018). Different classes of phenolic compounds serve different functions.…”
Section: Discussionmentioning
confidence: 99%
“…K. pinnata is rich in phenolic compounds, which account for some of these biological activities (25). The composition of phenolics can vary according to light conditions (33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%